Echocardiographic Prognosis Relevance of Attenuated Right Heart Remodeling in Idiopathic Pulmonary Arterial Hypertension - Zhao, Qin-Hua; Gong, Su-Gang; Jiang, Rong; Li, Chao; Chen, Ge-Fei; Luo, Ci-Jun; Qiu, Hong-Ling; Liu, Jin-Ming; Wang, Lan; Zhang, Rui (Frontiers in Cardiovascular Medicine, 2021)
Background: Right ventricular (RV) function is a great determination of the fate in patients with pulmonary arterial hypertension (PAH). Monitoring RV structure back to normal or improvement should be useful for evaluation of RV function. The aims of this study were to assess the prognostic relevance of changed right heart (RH) dimensions by echocardiography and attenuated RH remodeling (ARHR) in idiopathic PAH (IPAH). Methods: We retrospectively analyzed 232 consecutive adult IPAH patients at baseline assessment, included RH catheterization and echocardiography. ARHR at the mean 20±12 months follow-up was defined by a decreased right atrium area, RV mid diameter and left ventricular end-diastolic eccentricity index. The follow-up end point was all-cause mortality. Results: At mean 20±12 months follow-up, 33 of 232 patients (14.2%) presented with ARHR. The remaining 199 surviving patients were monitored for another 25±20 months. At the end of follow-up, the survival rates at 1, 3, and 5 years were 89%, 89% and 68% in patients with ARHR, respectively, 84%, 65% and 41% in patients without ARHR (Log rank p =0.01). ARHR was an independent prognostic factor for mortality. Besides, ARHR was available to further stratify patients’ risk assessment through the French PAH noninvasive risk criteria. Conclusions: Echocardiographic ARHR is an independent determinant of prognosis in IPAH at long term follow-up. ARHR might be a useful tool to indicate the RV morphologic and functional improvement associated with better prognostic likelihood.